Dynamic methylation adjustment and counting as part of imprinting mechanisms. - Shemer, R (1996)
Monoallelic expression in diploid mammalian cells appears to be a widespread phenomenon, with the most studied examples being X-chromosome inactivation in eutherian female cells and genomic imprinting in the mouse and human. Silencing and methylation of certain sites on one of the two alleles in somatic cells is specific with respect to parental source for imprinted genes and random for X-linked genes. We report here evidence indicating that: (i) differential methylation patterns of imprinted genes are not simply copied from the gametes, but rather established gradually after fertilization; (ii) very similar methylation patterns are observed for diploid, tetraploid, parthenogenic, and androgenic preimplantation mouse embryos, as well as parthenogenic and androgenic mouse embryonic stem cells; (iii) haploid parthenogenic embryos do not show methylation adjustment as seen in diploid or tetraploid embryos, but rather retain the maternal pattern. These observations suggest that differential methylation in imprinted genes is achieved by a dynamic process that senses gene dosage and adjusts methylation similar to X-chromosome inactivation.